The study of the pathogenicity of Brucella suis field isolate and transmission ability from pig to human - Agus Sudibyo (Jurnal Ilmu Ternak dan Veteriner, 1998)
The aim of this work was to study the pathogenicity of Brucella suis field isolate and its ability to transmit the disease from pig to human. The transmission ability of field isolate of B. suis was studied by using 4 brucellosis negative pigs which were put together with one of the artificially infected pig. The transmission ability of the diseases from pig to human was carried out by collecting blood samples from pigs and from the workers of pig farms and abattoir and tested them with the Rose Bengal Plate Test. The result indicated that field isolate of B. suis biotype 1 was pathogenic for pigs with the ID50 of 500 CFU. The infection was widely distributed into several organs or lymphnodes such as retropharingeal, submaxillaris, femoralis, suprascapularis, supramamaria and the spleen. The transmission of brucellosis from artificially infected pigs to negative pig in the group occurred between 4-6 weeks after they were put together. Brucellosis in the pigs was transmittable and causing brucellosis to workers of pig farms and abattoir. Key words : Brucella suis, pathogenicity, transmission, pig, human